ANALISIS PERTUMBUHAN PERUSAHAN, PROFITABILITAS, DAN LEVERAGE SEBAGAI FAKTOR PEMBERIAN OPINI AUDIT GOING CONCERN - anggun al araaf widiyanegara (Universitas Negeri Surabaya, 2020)
This research was conducted to determine the effect of company growth, profitability, and leverage on the going concern audit opinion. The sample in this study are mining companies listed on the Indonesia Stock Exchange. The research method used is quantitative with a purposive sampling technique, there are 31 companies that become research samples with the 2013-2018 observation period. The data analysis method used is Logistic Regression Analysis. The results showed that profitability affected the going concern audit opinion while company growth and leverage had no effect on giving going concern audit opinions.Keywords: Company Growth, Profitability, Leverage, Going Concern Audit Opinion